2017
DOI: 10.1063/1.4983452
|View full text |Cite
|
Sign up to set email alerts
|

A first-principles study of carbon-related energy levels in GaN. I. Complexes formed by substitutional/interstitial carbons and gallium/nitrogen vacancies

Abstract: Various forms of carbon based complexes in GaN are studied with first-principles calculations employing Heyd-Scuseria-Ernzerhof hybrid functional within the framework of density functional theory. We consider carbon complexes made of the combinations of single impurities, i.e. CN − CGa, CI − CN and CI − CGa, where CN, CGa and CI denote C substituting nitrogen, C substituting gallium and interstitial C, respectively, and of neighboring gallium/nitrogen vacancies (VGa/VN), i.e. CN − VGa and CGa − VN. Formation e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 62 publications
8
69
0
Order By: Relevance
“…The former is obtained by thermal techniques such as DLTS, whereas the latter is obtained by optical techniques such as DLOS. In our previous paper 5 , we assigned the origins of these experimentally observed trap levels to the calculated results obtained by our HSE calculations for carbon-carbon/carbon-vacancy complexes. These assignments are also presented in the right column of Table I.…”
Section: A Comparison With Experimental Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…The former is obtained by thermal techniques such as DLTS, whereas the latter is obtained by optical techniques such as DLOS. In our previous paper 5 , we assigned the origins of these experimentally observed trap levels to the calculated results obtained by our HSE calculations for carbon-carbon/carbon-vacancy complexes. These assignments are also presented in the right column of Table I.…”
Section: A Comparison With Experimental Resultsmentioning
confidence: 79%
“…In case of the 3+ charge state, the C atom forms a type 3 split interstitial sharing the site with an N atom making a dimer, which is defined in Ref. 5. This configuration is shown in Fig.…”
Section: Complexes Of Silicon With Carbonmentioning
confidence: 95%
See 1 more Smart Citation
“…Carbon, which is also present in high concentrations in our samples, can also form complexes with either V Ga or V N , but such complexes possess very high formation energies. 20 A more plausible hypothesis would be the formation of Si-related complexes. As a matter of fact, it was shown that a V Ga -complex, formed with Si, gives rise to an acceptor in FIG.…”
Section: Resultsmentioning
confidence: 99%
“…19 For these reasons, the hypothesis of an impurity (C or H)-related complex might be favored. As a matter of fact, a DFT study performed by Matsubara and Bellotti 20 reported a level at E C -0.22 eV for the C Ga V N complex.…”
Section: -2mentioning
confidence: 99%